Global Trends in Pro-Environmental Purchasing Intentions: Insights from an Analytical Examination - Escobar-Farfan, M (John Wiley and Sons Inc, 2025)
Pro-environmental behavior approaches aim to minimize environmental degradation resulting from customer actions, a societal concern. This study aims to provide a complete overview of the trends regarding scientific research on pro-environmental purchasing intentions over the last three decades. The objective is to identify years of evolution, the most relevant and influential keywords, articles, journals, universities, publishers, countries or regions, and authors. For this purpose, the work uses the Web of Science Core Collection database. It analyses a wide range of bibliometric indicators, including the number of publications and citations, citations per paper, the h-index, and citation thresholds. The study also develops a graphical analysis of bibliographical material using the visualization of similarities (VOS) viewer software. We present a bibliometric analysis using evaluative and relational techniques, reviewing measures, associations, and cauterization from 1995 to 2023. Our findings reveal a notable convergence of consumer behavior and environmental responsibility since the 2000s. The findings suggest the identification of three clusters of pro-environmental purchasing intention research: Customers perception of the value of sustainable products, the Theory of Planned Behavior, and Willingness to pay. The number of publications on the theme has exponentially increased since 2017. Research on pro-environmental purchasing intentions is conducted in various fields, including business, environmental sciences, green sustainable science and technology, environmental studies, and management. Therefore, this research provides a comprehensive understanding of patterns of pro-environmental purchasing intentions, which can inform further research. © 2025 John Wiley & Sons Ltd.